Ceramic reinforced aluminum alloy material and method for manufacturing the same

CN122898762APending Publication Date: 2026-10-13BEIJING SANWEI TECH DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611247738.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明目的在于提供一种陶瓷增强铝合金材料及其制备方法,以解决现有技术中存在的相关技术问题

Benefits of technology

(1)本发明中外密内疏陶瓷骨架内层采用60~80μm的大粒径造孔剂进行造孔,因此其内部孔隙尺寸更大;而外层则是采用20~40μm的小粒径造孔剂进行造孔,因此外层的孔隙尺寸较小,即形成致密的SiC外层。致密的SiC外层可作为承载外壳,避免在加压渗透过程中陶瓷骨架坍塌,有利于保障陶瓷骨架的稳定性和完整性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and preparation method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of ceramic reinforced aluminum alloy materials and production method thereof, it is related to aluminum alloy material technical field.The application discloses a kind of aluminum alloy melt, and the aluminum alloy melt is injected into the mold, and the aluminum alloy melt is injected into the mold.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy materials technology, specifically to a ceramic-reinforced aluminum alloy material and its preparation method. Background Technology

[0002] Aluminum alloys are widely used in high-end equipment manufacturing fields such as aerospace, rail transportation, automobile manufacturing, and precision machinery due to their advantages such as low density, high specific strength, excellent plasticity, good processing performance, and corrosion resistance. However, conventional aluminum alloys have drawbacks such as low hardness and poor wear resistance, which cannot effectively meet the application requirements under harsh conditions such as heavy load, high speed, and friction and wear.

[0003] Traditional methods for improving the hardness and wear resistance of aluminum alloys usually involve adding ceramic particles or fibers to the molten aluminum alloy. However, the aluminum alloys prepared by this method suffer from a significant reduction in toughness and impact resistance, making them extremely prone to brittle fracture.

[0004] Based on this, the present invention provides a ceramic-reinforced aluminum alloy material that combines hardness, toughness, and impact resistance, and its preparation method, which is of great significance. Summary of the Invention

[0005] The purpose of this invention is to provide a ceramic-reinforced aluminum alloy material and its preparation method, so as to solve the related technical problems existing in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: A method for preparing ceramic-reinforced aluminum alloy material includes the following steps: S1: Preparation of a ceramic framework with a dense outer layer and a sparse inner layer: S11: SiC micro powder, large particle size pore-forming agent, polycarbosilane, and dispersant are added to tetrahydrofuran, stirred and mixed, and after the tetrahydrofuran has completely evaporated, it is pressed into a blank to obtain the inner layer blank. S12: SiC micro powder, small particle size pore-forming agent, polycarbosilane, and dispersant are added to tetrahydrofuran, stirred and mixed, and then coated onto the surface of the inner layer blank. After drying, an outer layer is formed, resulting in a ceramic skeleton blank with a dense outer layer and a sparse inner layer. S13: The ceramic skeleton blank with a dense outer layer and a sparse inner layer is subjected to thermal oxidation treatment and sintering to obtain a ceramic skeleton with a dense outer layer and a sparse inner layer. S2: After pretreatment, the ceramic skeleton with a dense outer layer and a sparse inner layer is electroless nickel plating to obtain a nickel-plated ceramic skeleton. S3: Place the nickel-plated ceramic skeleton in a mold, inject molten aluminum alloy into it, pressurize and penetrate, and heat treat to obtain ceramic-reinforced aluminum alloy material.

[0007] Preferably, the preparation method of the outer dense and inner sparse ceramic skeleton is as follows: (1) SiC micro powder, large particle size pore-forming agent, polycarbosilane, and dispersant are added to tetrahydrofuran and stirred and mixed at 60~70℃ until the tetrahydrofuran is completely volatilized to obtain inner layer mixed powder; the inner layer mixed powder is added to a mold and pressed at 40~60MPa for 2~3min to form a blank to obtain an inner layer blank; (2) SiC micro powder, small particle size pore-forming agent, polycarbosilane, and dispersant are added to tetrahydrofuran and stirred and mixed for 2~4h to obtain (3) Apply the outer layer mixed slurry evenly to the surface of the inner layer blank. It can be applied multiple times. After each application, it needs to be kept at 60~70℃ for 1 hour to form the outer surface layer and obtain the outer dense and inner loose ceramic skeleton blank; (4) In the air atmosphere, heat the outer dense and inner loose ceramic skeleton blank to 150~170℃ and keep it for 2~4 hours, then raise the temperature to 180~200℃ and keep it for 3~6 hours. Then transfer it to the nitrogen atmosphere, raise the temperature to 1100~1200℃ and keep it for 2~4 hours, and then cool it in the furnace to obtain the outer dense and inner loose ceramic skeleton.

[0008] Preferably, the mass ratio of SiC micro powder, large particle size pore-forming agent, polycarbosilane, dispersant, and tetrahydrofuran is (90~100):(18~24):(12~18):(1~2):(220~280).

[0009] Preferably, the mass ratio of SiC micro powder, small particle size pore-forming agent, polycarbosilane, dispersant and tetrahydrofuran is (90~100):(10~15):(14~20):(1~2):(220~280).

[0010] Preferably, the particle size of the SiC micro powder is 10~20μm.

[0011] Preferably, the large-particle-size pore-forming agent and the small-particle-size pore-forming agent are cellulose micro powders of different particle sizes; wherein, the particle size of the large-particle-size pore-forming agent is 60~80μm; and the particle size of the small-particle-size pore-forming agent is 20~40μm.

[0012] Preferably, the dispersant is TH-908 ceramic dispersant.

[0013] Preferably, the thickness of the outer layer is 1.5~4mm.

[0014] Preferably, the preparation method of the nickel-plated ceramic skeleton is as follows: (1) Immerse the outer dense and inner loose ceramic skeleton in acetone for 10-20 min, take it out, and soak and clean it with deionized water for 1-2 h to complete the cleaning; (2) After cleaning, immerse the outer dense and inner loose ceramic skeleton in stannous chloride solution at 50-60℃ for 0.5-1 h, take it out, and soak and clean it with deionized water for 1-2 h; then immerse it in palladium chloride solution and continue to soak it at 50-60℃ for 0.5-1 h, take it out, soak and clean it with deionized water for 1-2 h, and finally dry it at 80-100℃ for 2-4 h to obtain the pretreated outer dense and inner loose ceramic skeleton; (3) Immerse the pretreated outer dense and inner loose ceramic skeleton in chemical nickel plating solution for nickel plating, take it out, clean it with deionized water, and dry it at 80-100℃ for 2-4 h to obtain the nickel-plated ceramic skeleton.

[0015] Preferably, the concentration of stannous chloride in the stannous chloride solution is 15~25 g / L.

[0016] Preferably, the concentration of palladium chloride in the palladium chloride solution is 0.4~0.6 g / L.

[0017] Preferably, the electroless nickel plating solution comprises the following raw material components at the following concentrations: nickel chloride 20-25 g / L, sodium hypophosphite 23-28 g / L, sodium citrate 30-40 g / L, sodium acetate 10-14 g / L, and deionized water as the solvent.

[0018] Preferably, the relevant parameters for the electroless nickel plating are: nickel plating temperature of 80~90℃, nickel plating time of 1~2h, and nickel plating pH of 4.6~5.0.

[0019] Preferably, the temperature of the molten aluminum alloy is 710~750℃.

[0020] Preferably, the pressure of the pressurized permeation is 65~85MPa, and the pressure holding time is 15~30min.

[0021] Preferably, the heat treatment method is as follows: after the furnace cools to 500~530℃ and holds for 2~4 hours, water quench, then heat up to 160~180℃ and holds for 6~10 hours, and air cool.

[0022] A ceramic-reinforced aluminum alloy material is prepared by the above-described preparation method.

[0023] Compared with the prior art, the beneficial effects of the present invention are: (1) In this invention, the inner layer of the ceramic skeleton, which is dense on the outside and sparse on the inside, is formed by using a pore-forming agent with a large particle size of 60~80μm, resulting in a larger internal pore size; while the outer layer is formed by using a pore-forming agent with a small particle size of 20~40μm, resulting in a smaller pore size, thus forming a dense SiC outer layer. The dense SiC outer layer can serve as a supporting shell, preventing the ceramic skeleton from collapsing during pressurized infiltration, which helps to ensure the stability and integrity of the ceramic skeleton.

[0024] (2) Due to the larger pore size inside the dense ceramic skeleton, more aluminum alloy melt can be infiltrated inside, thus greatly preserving the toughness and impact resistance of aluminum or aluminum alloy; while the pore size outside is lower, less aluminum alloy melt can be infiltrated outside, and under the action of the dense SiC outer layer, a high hardness and high wear resistance outer layer can be formed; finally, a ceramic-reinforced aluminum alloy material with hard exterior and tough interior is obtained by comprehensive preparation.

[0025] (3) Before sintering, the ceramic skeleton blank with a dense outer layer and a loose inner layer was subjected to low-temperature thermal oxidation treatment. Low-temperature thermal oxidation treatment can promote the full cross-linking of polycarbosilane, so as to achieve non-melting and shaping of the ceramic skeleton blank, thereby effectively avoiding the collapse of the ceramic skeleton blank structure caused by the melting of polycarbosilane during high-temperature pyrolysis. At the same time, it can also remove residual solvent in advance, reduce the risk of gas cracking during sintering, greatly improve the ceramic yield of polycarbosilane and ensure the structural stability of the ceramic skeleton.

[0026] (4) The present invention uses chemical nickel plating on the ceramic skeleton with dense outer layer and sparse inner layer. The nickel layer on the ceramic skeleton can improve the wettability between the aluminum alloy melt and the ceramic skeleton. At the same time, it can also inhibit the direct contact between the SiC ceramic skeleton and the aluminum alloy melt and the generation of unstable Al4C3 interface phase at the interface. It has a significant effect on enhancing the interfacial bonding strength between the aluminum alloy melt and the SiC ceramic skeleton.

[0027] (5) After casting, the present invention keeps the aluminum alloy at 500~530℃ for 2~4h, quenches it with water, and then raises the temperature to 160~180℃ and keeps it for 6~10h. The aluminum alloy can be strengthened by solution treatment, thereby improving the overall strength of ceramic reinforced aluminum alloy materials. At the same time, it can also eliminate the internal stress of forming and improve the structural stability of ceramic reinforced aluminum alloy materials.

[0028] In summary, this invention has comprehensively prepared a ceramic-reinforced aluminum alloy material with high surface hardness and high wear resistance, good internal toughness, and stable dimensional structure, characterized by "external hardness and internal toughness". Detailed Implementation

[0029] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] In the following examples, SiC micro powder with an average particle size of 15 μm; cellulose micro powder with average particle sizes of 70 μm and 30 μm; polycarbosilane with an oxygen content ≤0.6 wt%, an average molecular weight of 1500, and a ceramic yield ≥55%; TH-908 ceramic dispersant; stannous chloride; palladium chloride; nickel chloride; sodium hypophosphite; sodium citrate; sodium acetate; ZL101 aluminum alloy ingot, grade ZAlSi7Mg, with the following chemical composition: Si 7 wt%, Mg 0.35 wt%, Fe 0.25 wt%, Cu 0.08 wt%, Mn 0.25 wt%, Zn 0.2 wt%, Ti 0.08 wt%, Zr 0.08 wt%, Be 0.07 wt%, Sn 0.01 wt%, Pb 0.03 wt%, Y 0.15 wt%, with the balance being Al; and other raw materials were all commercially available.

[0031] Preliminary preparations: 1. Preparation of stannous chloride solution: Prepare the solution according to the following proportions of raw material components. Add 20g of stannous chloride to 160mL of 37wt% concentrated hydrochloric acid, stir and mix well, then add deionized water and make up to 1L to obtain a 20g / L stannous chloride solution. 2. Preparation of palladium chloride solution: Prepare the solution according to the following proportions of raw material components. Add 0.5g of palladium chloride to 100mL of 37wt% concentrated hydrochloric acid, stir and mix well, then add deionized water and make up to 1L to obtain a palladium chloride solution of 0.6g / L. 3. Preparation of electroless nickel plating solution: Prepare the solution according to the following proportions of raw materials: Add 35g sodium citrate and 12g sodium acetate to 500mL deionized water and stir to obtain solution A; add 23g nickel chloride to 150mL deionized water and stir to obtain solution B; add sodium hypophosphite to 150mL deionized water and stir to obtain solution C; first slowly add solution B to solution A and stir for 15min, then slowly add solution C and stir for 15min, add deionized water, and make up to 1L to obtain the electroless nickel plating solution.

[0032] Example 1: A method for preparing a ceramic-reinforced aluminum alloy material, comprising the following steps: S1: Preparation of a dense outer and sparse inner ceramic skeleton: (1) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 70μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran, stir and mix at 65℃ until the tetrahydrofuran is completely volatilized to obtain an inner layer mixed powder; add the inner layer mixed powder into a mold, press it at 50MPa for 3min, and press it into a blank to obtain an inner layer blank with a length of 5.5cm × width of 1cm × height of 1cm, wherein the mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:21:15:1.5:250; (2) Add SiC micro powder with an average particle size of 15μm and cellulose micro powder with an average particle size of 30μm to a mold. 1. Add polycarbosilane and TH-908 ceramic dispersant to tetrahydrofuran and stir for 3 hours to obtain an outer layer mixed slurry. The mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant and tetrahydrofuran is 95:12.5:17:1.5:250. (3) Coat the outer layer mixed slurry evenly on the surface of the inner layer blank repeatedly. After each coating, keep it at 65°C for 1 hour to form a 2mm thick outer layer and obtain a dense outer and sparse inner ceramic skeleton blank. (4) In an air atmosphere, heat the dense outer and sparse inner ceramic skeleton blank to 160°C and keep it for 3 hours. Then raise the temperature to 190°C and keep it for 4.5 hours. Then transfer it to a nitrogen atmosphere and raise the temperature to 1150°C and keep it for 3 hours. Then cool it in the furnace to obtain a dense outer and sparse inner ceramic skeleton. S2: Preparation of nickel-plated ceramic skeleton: (1) Immerse the outer dense and inner loose ceramic skeleton in acetone for 15 min, take it out, and soak it in deionized water for 1.5 h to complete the cleaning; (2) After cleaning, immerse the outer dense and inner loose ceramic skeleton in 20 g / L stannous chloride solution at 55°C for 0.5 h, take it out, and soak it in deionized water for 1.5 h; then immerse it in 0.5 g / L palladium chloride solution and continue to soak it at 55°C for 0.5 h, take it out, and soak it in deionized water for 1.5 h, and finally dry it at 90°C for 3 h to obtain the pretreated outer dense and inner loose ceramic skeleton; (3) Heat the chemical nickel plating solution to 85°C, add dilute hydrochloric acid or dilute ammonia to adjust the pH to 4.7, then immerse the pretreated outer dense and inner loose ceramic skeleton in it, take it out after soaking for 1.5 h, wash it with deionized water, and dry it at 90°C for 3 h to obtain the nickel-plated ceramic skeleton; S3: Add ZL101 aluminum alloy ingots to 730℃ to obtain ZL101 aluminum alloy melt; place nickel-plated ceramic skeleton in mold, pour ZL101 aluminum alloy melt at 730℃ into it, pressurize and penetrate at 75MPa for 25min, then let it cool to 515℃ and hold for 3h, water quench, then heat to 170℃ and hold for 8h to obtain ceramic reinforced aluminum alloy material.

[0033] The following is a control experiment based on Example 1, with comparative examples 1 to 5, as detailed below: Comparative Example 1: Comparative Example 1 is based on Example 1, with the following adjustments: both the outer and inner layers use cellulose micropowder with an average particle size of 30 μm, while other processes remain unchanged. Specifically: A method for preparing ceramic-reinforced aluminum alloy material includes the following steps: S1: Preparation of a dense outer and sparse inner ceramic skeleton: (1) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 30μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran, stir and mix at 65℃ until the tetrahydrofuran is completely volatilized to obtain an inner layer mixed powder; add the inner layer mixed powder into a mold, press it at 50MPa for 3min, and press it into a blank to obtain an inner layer blank with a length of 5.5cm × width of 1cm × height of 1cm, wherein the mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:21:15:1.5:250; (2) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 30μm to tetrahydrofuran, and cellulose micro powder with an average particle size of 30μm to tetrahydrofuran. 1. Add polycarbosilane and TH-908 ceramic dispersant to tetrahydrofuran and stir for 3 hours to obtain an outer layer mixed slurry. The mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant and tetrahydrofuran is 95:12.5:17:1.5:250. (3) Coat the outer layer mixed slurry evenly on the surface of the inner layer blank repeatedly. After each coating, keep it at 65°C for 1 hour to form a 2mm thick outer layer and obtain a dense outer and sparse inner ceramic skeleton blank. (4) In an air atmosphere, heat the dense outer and sparse inner ceramic skeleton blank to 160°C and keep it for 3 hours. Then raise the temperature to 190°C and keep it for 4.5 hours. Then transfer it to a nitrogen atmosphere and raise the temperature to 1150°C and keep it for 3 hours. After furnace cooling, obtain a dense outer and sparse inner ceramic skeleton.

[0034] Comparative Example 2: Comparative Example 2 is based on Example 1, with the following adjustment: no outer surface layer is provided, while other processes remain unchanged. Specifically: A method for preparing ceramic-reinforced aluminum alloy material includes the following steps: S1: Preparation of ceramic skeleton: (1) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 70μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran, stir and mix at 65℃ until the tetrahydrofuran is completely volatilized to obtain inner layer mixed powder; add the inner layer mixed powder into the mold, press it at 50MPa for 3min, and press it into a blank to obtain an inner layer blank with a length of 5.5cm × width of 1cm × height of 1cm, wherein the mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:21:15:1.5:250; (2) In an air atmosphere, heat the inner layer blank to 160℃ and hold for 3h, then raise the temperature to 190℃ and hold for 4.5h, then transfer it to a nitrogen atmosphere, raise the temperature to 1150℃ and hold for 3h, and furnace cool to obtain ceramic skeleton.

[0035] Comparative Example 3: Comparative Example 3 is based on Example 1, with the following adjustment: chemical nickel plating is not performed, while other processes remain unchanged. Specifically: A method for preparing ceramic-reinforced aluminum alloy material includes the following steps: S1: Preparation of a dense outer and sparse inner ceramic skeleton: (1) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 70μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran, stir and mix at 65℃ until the tetrahydrofuran is completely volatilized to obtain an inner layer mixed powder; add the inner layer mixed powder into a mold, press it at 50MPa for 3min, and press it into a blank to obtain an inner layer blank with a length of 5.5cm × width of 1cm × height of 1cm, wherein the mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:21:15:1.5:250; (2) Add SiC micro powder with an average particle size of 15μm and cellulose micro powder with an average particle size of 30μm to a mold. 1. Add polycarbosilane and TH-908 ceramic dispersant to tetrahydrofuran and stir for 3 hours to obtain an outer layer mixed slurry. The mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant and tetrahydrofuran is 95:12.5:17:1.5:250. (3) Coat the outer layer mixed slurry evenly on the surface of the inner layer blank repeatedly. After each coating, keep it at 65°C for 1 hour to form a 2mm thick outer layer and obtain a dense outer and sparse inner ceramic skeleton blank. (4) In an air atmosphere, heat the dense outer and sparse inner ceramic skeleton blank to 160°C and keep it for 3 hours. Then raise the temperature to 190°C and keep it for 4.5 hours. Then transfer it to a nitrogen atmosphere and raise the temperature to 1150°C and keep it for 3 hours. Then cool it in the furnace to obtain a dense outer and sparse inner ceramic skeleton. S2: Add ZL101 aluminum alloy ingots to 730℃ to obtain ZL101 aluminum alloy melt; place the outer dense and inner loose ceramic skeleton in the mold, pour in the ZL101 aluminum alloy melt at 730℃, pressurize and penetrate at 75MPa for 25min, then let it cool in the furnace to 515℃ and hold for 3h, water quench, and then heat to 170℃ and hold for 8h to obtain ceramic reinforced aluminum alloy material.

[0036] Comparative Example 4: Comparative Example 4 is based on Example 1, with the following adjustments: the ceramic skeleton blank with a dense outer layer and a sparse inner layer is sintered only in a nitrogen atmosphere without thermal oxidation treatment, while other processes remain unchanged. Specifically: A method for preparing ceramic-reinforced aluminum alloy material includes the following steps: S1: Preparation of a dense outer and sparse inner ceramic skeleton: (1) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 70μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran, stir and mix at 65℃ until the tetrahydrofuran is completely volatilized to obtain an inner layer mixed powder; add the inner layer mixed powder into a mold, press it at 50MPa for 3min, and press it into a blank to obtain an inner layer blank with a length of 5.5cm × width of 1cm × height of 1cm, wherein the mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:21:15:1.5:250; (2) Add SiC micro powder with an average particle size of 15μm, cellulose micro powder with an average particle size of 70μm, polycarbosilane, and TH-908 ceramic dispersant to tetrahydrofuran. SiC micro powder, cellulose micro powder with an average particle size of 30μm, polycarbosilane, and TH-908 ceramic dispersant are added to tetrahydrofuran and stirred for 3 hours to obtain an outer layer mixed slurry. The mass ratio of SiC micro powder, cellulose micro powder, polycarbosilane, TH-908 ceramic dispersant, and tetrahydrofuran is 95:12.5:17:1.5:250. (3) The outer layer mixed slurry is repeatedly and evenly coated on the surface of the inner layer blank. After each coating, it needs to be kept at 65℃ for 1 hour to form a 2mm thick outer layer, thus obtaining a dense outer and sparse inner ceramic skeleton blank. (4) In a nitrogen atmosphere, the dense outer and sparse inner ceramic skeleton blank is heated to 1150℃ and kept for 3 hours, then cooled in a furnace to obtain a dense outer and sparse inner ceramic skeleton.

[0037] Comparative Example 5: Comparative Example 5 is based on Example 1, with the following adjustment: after casting, no heat treatment is performed, while other processes remain unchanged. Specifically: S3: Add ZL101 aluminum alloy ingots to 730℃ to obtain ZL101 aluminum alloy melt; place nickel-plated ceramic skeleton in mold, inject ZL101 aluminum alloy melt at 730℃ into it, pressurize and penetrate at 75MPa for 25min, and then let it cool to room temperature to obtain ceramic reinforced aluminum alloy material.

[0038] Performance testing: The hardness and toughness of the ceramic-reinforced aluminum alloy materials prepared in Example 1 and Comparative Examples 1-5 were tested. The specific testing methods are as follows: (1) Hardness test: Apply a force of 187.5 kgf to a φ2.5 mm hard alloy ball indenter, press it into the surface of ceramic reinforced aluminum alloy material, hold for 15 s, perform hardness test, and take the average value of 3 test results; (2) Toughness test: GB / T 229-2020 was used as the test standard to test the impact toughness at 23℃. A V-notch specimen was used with an included angle of 45°, a root radius of 0.25mm, a ligament width of 8mm, a pendulum blade radius of 2mm, and an initial energy of 300J.

[0039] The results of the above performance tests are shown in Table 1 below: Table 1

[0040] Results Analysis: As can be seen from the data in Table 1, this invention prepares a structurally stable ceramic skeleton by combining a specific particle size pore-forming agent, thermal oxidation treatment, and nickel plating treatment. Aluminum alloy melt is then poured into the ceramic skeleton to comprehensively prepare a ceramic-reinforced aluminum alloy material with high surface hardness and high wear resistance, good internal toughness, and stable dimensional structure, characterized by "external hardness and internal toughness".

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a ceramic-reinforced aluminum alloy material, characterized in that: Includes the following steps: S1: Preparation of a ceramic framework with a dense outer layer and a sparse inner layer: S11: SiC micro powder, large particle size pore-forming agent, polycarbosilane, dispersant, and tetrahydrofuran are stirred and mixed until the tetrahydrofuran has completely evaporated, and then pressed into a blank to obtain the inner layer blank. S12: SiC micro powder, small particle size pore-forming agent, polycarbosilane, dispersant, and tetrahydrofuran are stirred and mixed evenly; then coated onto the surface of the inner layer blank to form the outer layer, resulting in a ceramic skeleton blank with a dense outer layer and a sparse inner layer. S13: The ceramic skeleton blank with a dense outer layer and a sparse inner layer is subjected to thermal oxidation treatment and sintering to obtain a ceramic skeleton with a dense outer layer and a sparse inner layer. S2: After pretreatment, the ceramic skeleton with a dense outer layer and a sparse inner layer is electroless nickel plating to obtain a nickel-plated ceramic skeleton. S3: Place the nickel-plated ceramic skeleton in a mold, inject molten aluminum alloy into it, pressurize and penetrate, and heat treat to obtain ceramic-reinforced aluminum alloy material; The large-particle-size pore-forming agent has a particle size of 60~80μm, and the small-particle-size pore-forming agent has a particle size of 20~40μm.

2. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The method for preparing the aforementioned dense outer and sparse inner ceramic framework is as follows: (1) SiC micro powder, large particle size pore-forming agent, polycarbosilane, dispersant and tetrahydrofuran are stirred and mixed at 60~70℃ until the tetrahydrofuran is completely volatilized to obtain inner layer mixed powder; the inner layer mixed powder is pressed into a blank to obtain inner layer blank; (2) SiC micro powder, small particle size pore-forming agent, polycarbosilane, dispersant and tetrahydrofuran are stirred and mixed to obtain an outer layer mixed slurry; (3) The outer layer of mixed slurry is uniformly coated on the surface of the inner layer blank to form an outer outer layer, resulting in a ceramic skeleton blank with a dense outer layer and a sparse inner layer. (4) In an air atmosphere, the ceramic skeleton blank with a dense outer layer and a loose inner layer is heated to 150~170℃ and held for 2~4h, then heated to 180~200℃ and held for 3~6h, then transferred to a nitrogen atmosphere, heated to 1100~1200℃ and held for 2~4h, then cooled in the furnace to obtain a ceramic skeleton with a dense outer layer and a loose inner layer. The mass ratio of SiC micro powder, large particle size pore-forming agent, polycarbosilane, dispersant and tetrahydrofuran is (90~100):(18~24):(12~18):(1~2):(220~280); The mass ratio of SiC micro powder, small particle size pore-forming agent, polycarbosilane, dispersant and tetrahydrofuran is (90~100):(10~15):(14~20):(1~2):(220~280).

3. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The SiC micro powder has a particle size of 10~20μm; the large-particle-size pore-forming agent and the small-particle-size pore-forming agent are cellulose micro powders of different particle sizes; the dispersant is TH-908.

4. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The thickness of the outermost layer is 1.5~4mm.

5. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The electroless nickel plating solution comprises the following raw material components at the following concentrations: nickel chloride 20~25g / L, sodium hypophosphite 23~28g / L, sodium citrate 30~40g / L, sodium acetate 10~14g / L, and deionized water as the solvent. The relevant parameters for the electroless nickel plating are: plating temperature of 80~90℃, plating time of 1~2h, and plating pH of 4.6~5.

0.

6. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The temperature of the molten aluminum alloy is 710~750℃.

7. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The pressure for the pressurized osmosis is 65~85MPa, and the pressure holding time is 15~30min.

8. The method for preparing a ceramic-reinforced aluminum alloy material according to claim 1, characterized in that: The heat treatment method is as follows: after the furnace cools to 500~530℃, hold for 2~4 hours, quench with water, then heat up to 160~180℃ and hold for 6~10 hours, and then air cool.

9. The ceramic-reinforced aluminum alloy material prepared by the method for preparing ceramic-reinforced aluminum alloy material according to any one of claims 1 to 8.